FROM LEX IULIA MUNICIPALIS TO FLAVIAN LEGES MUNICIPALES. DEVELOPMENT OF ROMAN MUNICIPAL ADMINISTRATION FROM CESAR TO DOMITIAN - Twarowska-Antczak, Emilia (Studia Europaea Gnesnensia, 2014)
autoreferat rozprawy doktorskiej